THE ROLE OF ACCOUNTING CONSERVATISM IN EFFECTING THE PUBLIC LISTED PALESTINIAN BANKS MARKET VALUE IN LIGHT OF THE AMENDMENTS TO THE PALESTINIAN BANKING GOVERNANCE MANUAL ISSUED IN 2014 - Alwehwah, Loay M. M.; Barakat, Firas S. Q.; Mahmoud, Oroubah A. R. (International Journal of Accounting & Finance Review, 2022)
Using an analytical approach, the researcher examined the market value of all six publicly-traded Palestinian banks from 2009 to 2013 and 2015 to 2019. (PRM). A higher degree of accounting conservatism was found in the BTM model after the amendment, but no difference in the accrual model (TACC/EBXT) after the amendment, the study concluded. A positive role for BTM and Accrual models before the modifications, whereas a negative role for (TACC/EBXT) and (BTM). To ensure that reasonable degrees of accounting conservatism is applied in Palestinian banks, the researcher recommends that the Palestinian Monetary Authority (PMA) strengthen its control over financial policies adopted by Palestinian banks. So that bank financial statements are not exaggerated and are more reliable, the report urges the concerned authorities to issue legislation requiring the exercise of conservatism and requiring the external auditor to express his opinion on the level of conservatism practiced in bank financial statements. JEL Classification Codes: H83, G32, G21.